Variable-rate Fertilizer Based on a Fuzzy PID Control Algorithm in Coastal Agricultural Area - Song, Lepeng; Wen, Liangxian; Chen, Yongkang; Lan, Yang; Zhang, Junlin; Zhu, Jianqu (Journal of coastal research, 2020)
Song, L.; Wen, L.; Chen, Y.; Lan, Y.; Zhang, J., and Zhu, J., 2020. Variable-rate fertilizer based on a fuzzy PID control algorithm in coastal agricultural area. In: Yang, Y.; Mi, C.; Zhao, L., and Lam, S. (eds.), Global Topics and New Trends in Coastal Research: Port, Coastal and Ocean Engineering. Journal of Coastal Research, Special Issue No. 103, pp. 490–495. Coconut Creek (Florida), ISSN 0749-0208. Quantitative study on the system of variable-rate fertilizer in agricultural production helps to reduce use of fertilizer, preserve green environment, increase the economic benefit of agriculture, and achieve the sustainable development of agriculture. This study combined the conventional PID control and fuzzy control algorithms with the optimization of genetic algorithm to design the variable-rate fertilizer system. Then, with the prescription map, the speed and swath width of fertilizer application equipment were configurated to accurately control the amount of granular fertilizer applied in a field. The design was mathematically modeled and simulated with the programs of MATLAB (Math Works, Natick, MA). The conclusion as follows: not only do fuzzy control and the PID control based on the combination of genetic algorithm have quicker response speed and robust of anti-parameters change, it achieve high precision control and finally meets the requirement of the experiment purpose. With different quantitative granular fertilizer and speed of tumbrel, the model can well simulate precise control of variable-rate of the granular fertilizer of the tumbrel and uniform fertilizing.